Kredibilitas Influencer dan Citra Merek Berpengaruh terhadap Minat Beli Kosmetik Generasi Z di Kota Sukoharjo - Riska Ardiyani; Harsanto Harsanto; Indra Hastuti (Lembaga Pengembangan Kinerja Dosen, 2026)
The widespread use of social media has significantly transformed how consumers particularly Generation Z obtain information about cosmetic products. Marketing strategies leveraging influencers and reinforcing brand image have become key approaches for companies seeking to drive consumer purchase intention. This study examines the impact of influencer credibility and brand image on the purchase intention for cosmetic products among Generation Z in Sukoharjo Regency. Employing a quantitative approach, the study surveyed 100 respondents selected via purposive sampling based on criteria such as belonging to Generation Z and having prior experience purchasing cosmetic products. Data were collected using Google Forms and analyzed via Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. The results indicate that both influencer credibility and brand image exert a positive and significant influence on purchase intention for cosmetic products. Notably, brand image was found to contribute more significantly than influencer credibility to driving consumer purchase intention. These findings offer important implications for the cosmetics industry, highlighting the need for selectivity in choosing highly credible influencers while simultaneously strengthening brand image through targeted, effective marketing strategies designed to reach and engage Generation Z as a key market segment.